2000
DOI: 10.1007/pl00010299
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Assisted Stereoselective Synthesis and Antibacterial Activity of New Fluoroquinolinyl-β-lactam Derivatives

Abstract: A series of quinoline ring substituted N-(3-chloro-2-(2-¯uoro-quinolin-3-yl)-4-oxoazetidin-1-yl)-octanamides were synthesized from chloroacetyl chloride, octanoic acid, (2-¯uoro-quinolin-3-yl-methylene)-hydrazides, and triethylamine using microwave irradiation as well as conventional heating. The reaction time can be brought down from hours to minutes with improved yields using microwave irradiation compared to conventional heating. The compounds were tested for their in vitro antibacterial activity against 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…SAR study deduce that the substitution by β-lactam moiety in the 3 rd position of 2-fluoro quinoline increased the antibacterial potency. [87] In general, the aforementioned study concluded that hydrazide/hydrazone substitution at the 3 rd position of quinoline ring enhanced the antibacterial activity with huge potential as compared to substitution at the 1 st and 2 nd positions of quinoline ring. In many cases, these compounds showed equipotent activity as standard drugs.…”
Section: Aryl-substituted Quinoline Hydrazide/hydrazone Derivativesmentioning
confidence: 98%
See 1 more Smart Citation
“…SAR study deduce that the substitution by β-lactam moiety in the 3 rd position of 2-fluoro quinoline increased the antibacterial potency. [87] In general, the aforementioned study concluded that hydrazide/hydrazone substitution at the 3 rd position of quinoline ring enhanced the antibacterial activity with huge potential as compared to substitution at the 1 st and 2 nd positions of quinoline ring. In many cases, these compounds showed equipotent activity as standard drugs.…”
Section: Aryl-substituted Quinoline Hydrazide/hydrazone Derivativesmentioning
confidence: 98%
“…Amongst the studied compounds, 30 was the most potent compound (ZOI=21 mm) and showed significant activity in comparison to standard drug ampicillin (ZOI=16 mm) against 2340‐ Enterobacte r. Compound 30 also showed standard drug equivalent activity against 2491 ‐Erwinia herbicola (ZOI=21 mm). SAR study deduce that the substitution by β ‐lactam moiety in the 3 rd position of 2‐fluoro quinoline increased the antibacterial potency [87] …”
Section: Quinoline Hydrazide/hydrazone Derivatives As Antibacterial A...mentioning
confidence: 98%
“…Currently the use of microwave energy to accelerate organic reactions has been taken to a new dimension, is a matter of increasing interest and offers several advantages (10,11). Moreover the coupling of MWI with the use of inexpensive inorganic solid supported reagents (12,13) is consider as efficient, ecofriendly technology.…”
Section: Introductionmentioning
confidence: 99%
“…1 The use of microwave irradiation is an established tool in organic synthesis for achieving better selectivity, rate enhancement and reduction of thermal degradation byproducts. 2,3 However these procedures are practically limited as solvents in a microwave oven at elevated temperatures create high pressure, which may cause explosion. One of the advances to overcome this problem is inorganic 4,5 solid supported organic synthesis which attracts attention because of enhanced selectivity, milder reaction conditions and associated ease of manipulation.…”
Section: Introductionmentioning
confidence: 99%